SYMBOLISM IN WILLIAM BLAKE’S POETRY - Saggar, Nitika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
William Blake (1757–1827), an English Romantic poet and artist, is renowned for his symbolic and visionary approach to poetry. His works, including Songs of Innocence and Experience, The Marriage of Heaven and Hell, and Jerusalem, are rich in layered meanings that explore themes of innocence, experience, spirituality, and human consciousness. This paper examines the profound symbolism in Blake’s poetry, focusing on recurring motifs such as the lamb, the tiger, and the child, as well as his use of mythological and biblical references. Through an analysis of key poems, this study highlights how Blake’s symbolic language reflects his spiritual philosophy and critique of societal structures.